Knowledge Leadership and Innovation: The Mediating Role of Knowledge Sharing - Rahman, Mohammad Masudur; Röntynen, Rositsa; Ardabili, Farzad S.; Newaz, H. T. M. Quader; Voitenko, Elena; Cajnko, Petra (Journal of Ecohumanism, 2025)
This study investigates the relationship between knowledge leadership and innovation from the perspective of employees, with knowledge sharing serving as a mediating factor. A total of 160 randomly selected employees completed the questionnaire. After validating the measures, the data were analyzed using structural equation modeling. The results indicate that the components of knowledge leadership —namely leadership skills, participation and trust, and knowledge integration and innovation—have a significant positive effect on the speed of innovation and knowledge sharing. Additionally, knowledge sharing plays a significant mediating role in the relationship between knowledge leadership and innovation speed. These findings suggest that managers and organizational leaders can accelerate innovation by fostering knowledge sharing through the development of leadership skills and targeted leadership training.